2014
DOI: 10.1063/1.4864778
|View full text |Cite
|
Sign up to set email alerts
|

Unusual defect physics in CH3NH3PbI3 perovskite solar cell absorber

Abstract: Thin-film solar cells based on Methylammonium triiodideplumbate (CH3NH3PbI3) halide perovskites have recently shown remarkable performance. First-principle calculations show that CH3NH3PbI3 has unusual defect physics: (i) Different from common p-type thin-film solar cell absorbers, it exhibits flexible conductivity from good p-type, intrinsic to good n-type depending on the growth conditions; (ii) Dominant intrinsic defects create only shallow levels, which partially explain the long electron-hole diffusion le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

130
2,421
11
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,387 publications
(2,573 citation statements)
references
References 24 publications
130
2,421
11
11
Order By: Relevance
“…The furnace was preheated to 360 °C in zone 1 and 350 °C in zone 2. The substrates were loaded into the furnace in zone 2, but close to zone 1, and 300 mg BiI 3 was deposited on top by spin-casting a solution of 1 mol L −1 nickel nitrate hexahydrate (Sigma-Aldrich) in ethylene glycol with 1 mol L −1 ethylenediamine at 5000 rpm for 45 s. The films were annealed in air at 100 °C for 40 min, followed by 300 °C for 1 h. Following BiOI deposition on top, ZnO was deposited by AP-CVD. Diethylzinc (Sigma-Aldrich) was used as the Zn precursor, and 100 mL min −1 oxygen gas (Air Products, <3 ppm H 2 O) as the oxidant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The furnace was preheated to 360 °C in zone 1 and 350 °C in zone 2. The substrates were loaded into the furnace in zone 2, but close to zone 1, and 300 mg BiI 3 was deposited on top by spin-casting a solution of 1 mol L −1 nickel nitrate hexahydrate (Sigma-Aldrich) in ethylene glycol with 1 mol L −1 ethylenediamine at 5000 rpm for 45 s. The films were annealed in air at 100 °C for 40 min, followed by 300 °C for 1 h. Following BiOI deposition on top, ZnO was deposited by AP-CVD. Diethylzinc (Sigma-Aldrich) was used as the Zn precursor, and 100 mL min −1 oxygen gas (Air Products, <3 ppm H 2 O) as the oxidant.…”
Section: Methodsmentioning
confidence: 99%
“…[5,9,[11][12][13] Timecorrelated single photon counting (TCSPC) measurements of (CH 3 NH 3 ) 3 Bi 2 I 9 and Cs 2 AgBiBr 6 , among others, have shown that these materials exhibit lifetimes exceeding 1 ns. [11,15,16] This is significant because analysis of established thin-film solar absorbers has shown that materials with minority-carrier lifetimes of 1 ns or above have the potential to reach or exceed 10% efficiency.…”
mentioning
confidence: 99%
“…The latter would be responsible for nonradiative recombination acting as Shockley-Read-Hall nonradiative recombination centers. [147] This explains the origin of the excellent defect tolerance of these perovskite materials.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…11,12 Distortions of the inorganic lattice by halide substitution and octahedral tilting have been shown to influence the band gap and absorption properties. 7,[13][14][15] Although the A-cation does not contribute to electronic states near the band gap, [16][17][18] it has been shown to affect the nature of the band gap through interaction with the inorganic Pb−I sublattice. 19 Moreover, the dielectric properties of CH 3 NH 3 PbI 3 are linked to both the rotational dynamics and ordering of the molecular A-cation and the structural phase transitions of the inorganic Pb−I lattice.…”
Section: Introductionmentioning
confidence: 99%